Efficacy And Compatibility Of Blood-Mimicking Fluid In Vascular Wall-Less Flow Phantom For Use In Doppler Ultrasound Applications - Oglat, Ammar Anwar Khaled (2019)
Doppler ultrasound (US) tools have been utilized clinically and pre-clinically since 1970s, and they were extremely responsible for the detection of blood flow in arteries and veins. This project shows a general overview focusing on the measuring and calculating the influence of the thickness of protective layer in ultrasonic probe of German Society for Applied Medical Physics and Technology (GAMPT) for the speed of sound (Vs) measurements. Preparing and characterizing new BMF with relatively low-cost, suitable viscosity, and less consuming time for preparation with both new adequate ternary mixture fluid (water (H2O), propylene glycol (PG), and polyethylene glycol (PEG) 200Mw) and with a novel suspension scatter particle (Poly (4-methylstyrene)) to produce a suitable backscatter power comparable to the human blood were explained. Moreover, in this study, the mechanisms of fabrication and characterization a strong (robust) and elastic vascular wall-less flow phantom (TMM and VMM) utilizing a physically strong materials called Konjac (K), Carrageenan (C), and gelatin (bovine skin)-based TMM for high physiological flow rate and detection of the issues related to it by medical Doppler US were explained. The ultrasonic technique was utilized as a main apparatus for acoustical measurements (Vs, attenuation (α), and backscatter power) of BMF and TMM.